Does participation in university governance add value to a student's academic experience? - Mthethwa, V.; Chikoko, V. (South African Journal of Higher Education, 2020)
During the Apartheid period in South Africa, students at Historically Black Universities were excluded from participating in institutional decision-making affecting their enrollment, fee allocation, academic challenges and general well-being. The Higher Education Act of 1997, changed this situation to a participatory inclusion of the Student Representative Council in university governance where they could influence and promote students’ academic interests. This article draws from a study that was conducted at selected Black universities, to explore the academic benefits derived by students who participated in governance since the change. Issues of free education that have been topical in South Africa and further pose scrutiny on how this achievement is beneficial to the SRC who are central to student development advocacy. Adopting a qualitative research approach, the study sought to understand the academic experiences of the SRC, as participants in the highest decision-making structures at these institutions. Findings from the study suggest that the academic benefit for the SRC as participants in governance is dependent on their level of study, political deployment, time commitments and academic aspirations. There ought to be a deeper interrogation on how best to ensure academic value for students who participate in governance.